THE INFLUENCE OF WATCHING FOOTBALL MATCHES ON ACUTE CARDIOVASCULAR EVENTS - Jacek Sitkiewicz; Władysław Hryniuk; Julia Kwiecińska; Alicja Toczyłowska; Mateusz Muras; Łukasz Bialic; Lidia Madrzak; Marta Korchowiec; Katarzyna Krzyżanowska; Wiktor Chrzanowski (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Objective: Acute emotional stress with big football matches is recognized to precipitate cardiovascular events in some individuals. The purpose of this narrative review is to address the existing scientific evidence regarding the association of viewing football matches with the risk of cardiovascular events like myocardial infarction, arrhythmias, and sudden cardiac death.Methods: The review was based on an extensive PubMed database search conducted in April 2025. Articles were graded on methodology, sample description, scope of study, and results reported. There were no restrictions on publication dates. English-language studies and applicable book chapters only were considered.Conclusions: The studies indicate that emotionally charged matches - especially if spectators are strongly bonded or identify intensely with their team - can raise the risk of cardiovascular incidents, especially in men who have a background of cardiovascular illness. Population data are contentious, nevertheless, and additional confounding variables like alcohol consumption, smoking, and unhealthy diet might be involved. Healthy emotional reactions (e.g., victories) can be protective. The public health interventions should aim at reducing behaviour and offer emergency readiness in risk high-risk environments like stadiums or fan zones. The measures of public health should emphasize reducing risk behaviour and offer emergency preparedness in high-risk environments like stadiums.